Association between Active Mobility Index and sarcopenia among Japanese community‐dwelling older adults - Satoshi Kurita; Takehiko Doi; Kota Tsutsumimoto; Sho Nakakubo; Yuto Kiuchi; Kazuhei Nishimoto; Hiroyuki Shimada (Wiley, 2022)
Abstract Background A physically active lifestyle, including physical and social activities, is needed to maintain muscle mass, strength, and physical performance. A large life space characterizes an active lifestyle, but the association between life space with physical and social activities and sarcopenia is unclear. This study aimed to examine the association between life space with physical and social activities, assessed using the Active Mobility Index (AMI), and sarcopenia in community‐dwelling Japanese older adults. Methods This study used a large, cross‐sectional cohort dataset from the National Center for Geriatrics and Gerontology‐Study of Geriatric Syndromes (NCGG‐SGS). Between 2013 and 2018, community‐dwelling Japanese adults aged ≥60 years participated in the NCGG‐SGS. Sarcopenia was identified by measuring muscle mass and strength based on the clinical definition. The secondary outcomes were sarcopenia indices, including lower muscle mass, lower muscle strength, and lower gait speed. AMI assessed life space with physical and social activities in each life space (distance from the respondent's home: <1, 1-10, or >10 km) during the past month by noting the frequency, primary purpose, type of transportation, interaction with others, and physical activity. The associations between quartile groups of AMI total, physical, and social scores and sarcopenia were examined using a logistic regression model. Results From all participants, 21 644 participants (age 73.5 ± 5.8 years, 54.7% female) were included in the analysis. The prevalence of sarcopenia was 4.1% (n = 894). For the AMI total score, referred to Q1 group, Q3 and Q4 groups were significantly associated with a reduced odds ratio (OR) of sarcopenia after adjusting for all covariates [adjusted OR (aOR) (95% confidence interval), Q3: 0.71 (0.57-0.89), Q4: 0.69 (0.55-0.87)]. Q3 and Q4 of the AMI physical score groups were also significantly associated with reduced OR of sarcopenia [Q3: 0.71 (0.57-0.89), Q4: 0.67 (0.54-0.84)]. For the AMI social score, only the Q4 group showed reduced OR for sarcopenia [0.79 (0.62-1.01)]. Q3 and Q4 of the AMI total score and physical score were associated with reduced OR of all sarcopenia indices (aOR 0.55-0.82, all P < 0.05), whereas Q4 of AMI social score was associated with all indices (aOR 0.85-0.81, all P < 0.05). Conclusions The extent of life space with physical activity was associated with sarcopenia in community‐dwelling older adults. A longitudinal study is needed to examine whether life space with physical and social activities affect the development of sarcopenia.